2023
DOI: 10.1017/gmb.2023.5
|View full text |Cite
|
Sign up to set email alerts
|

White kidney bean extract as a nutraceutical: effects on gut microbiota, alpha-amylase inhibition, and user experiences

Abstract: White kidney bean extract (WKBE) is a nutraceutical often advocated as an anti-obesity agent. The main proposed mechanism for these effects is alpha-amylase inhibition, thereby slowing carbohydrate digestion and absorption. Thus, it is possible that WKBE could impact the gut microbiota and modulate gut health. We investigated the effects of supplementing 20 healthy adults with WKBE for 1 week in a randomised, placebo-controlled crossover trial on the composition of the gut microbiota, gastrointestinal (GI) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, a recent study showed discrepant results. A randomized placebo-controlled crossover trial of 20 healthy adults showed that 1 week of WKBE supplementation elevated the relative abundance of Bacteroidetes and reduced that of Firmicutes; however, no significant differences were observed in the gut microbiota composition between the WKBE and control treatment groups [44]. The duration of this intervention might be the main reason for different results.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed discrepant results. A randomized placebo-controlled crossover trial of 20 healthy adults showed that 1 week of WKBE supplementation elevated the relative abundance of Bacteroidetes and reduced that of Firmicutes; however, no significant differences were observed in the gut microbiota composition between the WKBE and control treatment groups [44]. The duration of this intervention might be the main reason for different results.…”
Section: Discussionmentioning
confidence: 99%